KLOTHO PROTEIN AND MITOCHONDRIAL SUPEROXIDE DISMUTASE IN YOUNG PERSONS WITH GASTROESOPHAGEAL REFLUX DISEASE AND AUTOIMMUNE THYROIDITIS - Zhdan, V.M.; Pasiieshvili, T.M.; Zhelezniakova, N.M.; Kovalyova, O.M.; Pasiieshvili, L.M. (World of Medicine and Biology, 2020)
The purpose of the work was to study the levels of the Klotho protein and mitochondrial superoxide dismutase in young patients with a comorbid course of gastroesophageal reflux disease and autoimmune thyroiditis. Study conducted 165 students: 120 with gastroesophageal reflux disease and autoimmune thyroiditis and 45 with isolated gastroesophageal reflux disease. Klotho protein and mitochondrial superoxide dismutase were studied in blood serum by enzyme immunoassay. The study of mitochondrial superoxide dismutase and Klotho protein showed a significant increase in these indicators in patients with gastroesophageal reflux disease and autoimmune thyroiditis in comparison with the control group and the group with isolated gastroesophageal reflux disease. The Klotho protein and mitochondrial superoxide dismutase can be used as biomarkers of gastroesophageal reflux disease progression in young patients with concomitant autoimmune thyroiditis.